Removing Methods of Ultracide Residues in Imported Apple Peels in Iraqi Local Markets - Sedik A.K. Al-Hiyaly1; Saba Riad Khudhaier 2; Jazzer, A, J. Al-Temmemi3; Ahmed S.A. Al-Tae1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The resides of ultracide insecticide used in controlling apple insets may have public health problems. This work was designed to find much effective method that capable of removing as much as possible of such residues from imported apple peels available in local markets. Imported apple samples were collected during winter 2018 from different local markets and divided into four subsamples as physical treatments where the first was left unwashed apple, the second was washed by tap water, the third was washed with saline solution and finally apple sample washed by tap water with acetic acid. Apple peels of all examined samples were left to dry in an oven at 85° C for 24 h and then powdered. 2.5 g from each sample was received 12.5 ml distil water to estimate the insecticide residues by using gas chromatography. It has been found that unwashed apple peels had the highest ultracide insecticide level followed by that which washed by tap water while the peels washed by saline water was obviously free from the insecticide residues.